EDUCATIONAL GUIDANCE IN PHRASEOLOGY AS A MEANS OF LINGUOCULTURAL COMPETENCY DEVELOPMENT OF FOREIGN STUDENTS - Nikitina, Tatiana; Rogaleva, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article covers the issues of linguocultural competency of foreign students based on the phraseological material. Ethnocultural content of the Russian phraseological units has been reviewed, as well as their connection to Russian history and culture. A dictionary-type educational guidance is presented as a means of development of the linguocultural competency.The structure of the dictionary entry is shown, parametric zones of which correlate with the components of the linguocultural competency - language and cultural knowledge, receptive and productive speaking skills. Results of the methodical experiment are presented proving the effectiveness of the educational guidance developed by the authors.